Modeling of interactive cooperation’s instrument “Virtual board” for project “Kherson Virtual University 2.0” - Kozlovskiy Є.О. (Journal of Information Technologies in Education (ITE), 2007)
In the article preconditions are considered for creation in the distance learning system studies the effective model of tutor and students co-operation. And also the description and principles of planning of similar models.